When Friendship Turns Sour: Effective Communication Between Mitochondria and Intracellular Organelles in Parkinson's Disease - Lin, Tsu-Kung; Lin, Kai-Jung; Lin, Kai-Lieh; Liou, Chia-Wei; Chen, Shang-Der; Chuang, Yao-Chung; Wang, Pei-Wen; Chuang, Jiin-Haur; Wang, Tzu-Jou (Frontiers in Cell and Developmental Biology, 2020)
Parkinson’s disease (PD) is a complex neurodegenerative disease with the pathological hallmarks: progressive neuronal loss from the substantia nigra pars compacta and α-synuclein intra-neuronal inclusions known as Lewy bodies. Although the etiology of PD remain elusive, mitochondrial damage has been established to take center stage in the pathogenesis of PD. Mitochondria are critical to cellular energy production, metabolism, homeostasis, and stress responses; the association with PD emphasizes the importance of maintenance for the mitochondria network integrity. To accomplish the pleiotropic functions, mitochondria are dynamic not only within their own network, but also in orchestrated coordination with other organelles in the cellular community. Through physical contact sites, signal transduction, and vesicle transport, mitochondria and intra-cellular organelles achieve goals of calcium homeostasis, redox homeostasis, protein homeostasis, autophagy and apoptosis. Here, we review the finely tuned interactions between mitochondria and surrounding intra-cellular organelles especially focusing on the nucleus, endoplasmic reticulum, golgi apparatus, peroxisomes, and lysosomes. Potential participants that may contribute to PD pathogenic mechanisms will be highlighted in this review.